2020
DOI: 10.7717/peerj.9458
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals a reprogramming energy metabolism-related signature to improve prognosis in colon cancer

Abstract: Although much progress has been made to improve treatment, colon cancer remains a leading cause of cancer death worldwide. Metabolic reprogramming is a significant ability of cancer cells to ensure the necessary energy supply in uncontrolled proliferation. Since reprogramming energy metabolism has emerged as a new hallmark of cancer cells, accumulating evidences have suggested that metabolism-related genes may serve as key regulators of tumorigenesis and potential biomarkers. In this study, we analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…High energy metabolism ( p = 0.0017) was associated with a better prognosis for LGG with high EMT. Patients with favorable clinical outcomes had low energy metabolic activity in UVM, STAD, HNSC, and LAML, ( Figure S4 ), and several studies have shown that a poor prognosis is observed in patients with high energy metabolic reprogramming [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…High energy metabolism ( p = 0.0017) was associated with a better prognosis for LGG with high EMT. Patients with favorable clinical outcomes had low energy metabolic activity in UVM, STAD, HNSC, and LAML, ( Figure S4 ), and several studies have shown that a poor prognosis is observed in patients with high energy metabolic reprogramming [ 32 ].…”
Section: Resultsmentioning
confidence: 99%